2012
DOI: 10.1177/1091581811431111
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Glargine: A Reevaluation of Rodent Carcinogenicity Findings

Abstract: The 1995 to 1997 lifetime carcinogenicity studies of insulin glargine in rats and mice were reanalyzed and reassessed for their validity according to current guidelines. In 2-year studies, 50 animals per sex and per group were used. Survival rates between weeks 80 and 90 in female mice and rats were greater than 20 animals in all groups, fulfilling current Food and Drug Administration requirements that enough animals lived long enough to provide adequate exposure to glargine and to be at risk of forming late-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In 2002, an animal study [34] that lasted for 2 years demonstrated that insulin glargine did not have a systemic cancerigenic potential in rats and mice. A recent study [35] by the same investigators reevaluating the carcinogenicity potential of insulin glargine indicated that cancer risk was found to be no greater for animals treated with insulin glargine than for the control-treated animals. They considered that insulin glargine was not likely to pose a cancer risk in humans and the findings needed to be confirmed by ongoing clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, an animal study [34] that lasted for 2 years demonstrated that insulin glargine did not have a systemic cancerigenic potential in rats and mice. A recent study [35] by the same investigators reevaluating the carcinogenicity potential of insulin glargine indicated that cancer risk was found to be no greater for animals treated with insulin glargine than for the control-treated animals. They considered that insulin glargine was not likely to pose a cancer risk in humans and the findings needed to be confirmed by ongoing clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, study conducted by Colmers et al revealed increased risk of pancreatic and prostate cancers in glargine users. On the contrary, several studies found that glargine did not increase carcinogenic risk [132,133]. It is also suggested that there is neutral relationship between glargine and overall/cancer-specific outcomes [134].…”
Section: Exogenous Insulin ▼mentioning
confidence: 99%
“…Conversely, it is important to note that many studies found that glargine did not increase carcinogenic risk, and a neutral link between glargine and overall/cancerspecific outcomes was also suggested [108][109][110].…”
Section: Insulin and Insulin Analogsmentioning
confidence: 99%